PENGARUH MEDIA SERBANEKA TERHADAP PEMAHAMAN MATERI AKHLAK DI PONDOK PESANTREN WALISONGO PUTRA CUKIR JOMBANG - Alan Ubaidirrohman, Ibnu (Al Tadib : Jurnal Ilmu Pendidikan, 2023)
: Miscellaneous media are expected to provide effective learning methods and generate feedback related to students' understanding of a material. Therefore, this research was conducted with the aim of 1) knowing the application of various media at the Walisongo Putra Cukir Jombang Islamic Boarding School, 2) knowing the level of understanding of moral material by students at the Walisongo Putra Cukir Jombang Islamic Boarding School and 3) knowing the effect of various media on understanding the material. morals at the Walisongo Putra Cukir Islamic Boarding School, Jombang. The research method uses a quantitative approach that is expost facto, with a research sample of 20 students. The research data were analyzed with the help of the SPSS version 16.0 application. The results showed that the multifarious media had been applied quite well, as seen from the increased enthusiasm of the students, but the results of the analysis showed that there was no significant influence in the application of the multifarious media on the understanding of moral material at the Walisongo Putra Cukir Jombang Islamic Boarding School.